O papel das Academias para o nascimento da elite intelectual na América Portuguesa - Simone Santana Rodrigues Elias; Décio Ruivo Martins (História - Revista da Faculdade de Letras da Universidade do Porto, 2017)
The main goal of this article is to introduce the participation of the Luso-Brazilian intellectual elite in the formation of literary societies and in the history of science in Portugal. Their developments led to the first collective manifestations of a local intelligence, bringing together graduates of European universities under the command of the Portuguese Crown. These scholars, born in a colony devoid of universities, were responsible for the emergence of the first, though short-lived, Academy of Sciences of the entire Portuguese Empire. To understand the birth of scientific practice in Brazil as an effort of its intellectual elite, it is necessary to pursue the thread of history that reveals its constitution.